Optical reflectivity and hardness improvement of hafnium nitride films via tantalum alloying - Gu, Zhiqing (2017)
It is found that incorporation of tantalum in a hafnium nitride film induces a tunable optical reflectivity and improves the hardness. The underlying mechanism can be illustrated by a combination of experiments and first-principles calculations. It is shown that the evolution of optical reflectivity and the increase in hardness arise from the formation of Hf1−xTaxN solid solutions and the resulting changes in the electronic structure. The increase in infrared reflectance originates from the increase in concentration of free electrons (n) because Ta (d3s2) has one more valence electron than Hf (d2s2). The sharp blue-shift in cutoff wavelength is attributed to the increase in n and the appearance of t2g → eg interband absorption. These results suggest that alloying of a second transition metal renders an effective avenue to improve simultaneously the optical and mechanical properties of transition metal nitride films. This opens up a door in preparing high-reflectance yet hard films.